Application of Problem-Based Learning Model for Improving Students Understanding of Human Rights Concepts at Class VII Students of SMP Neg. 29 Rumbia - Agus, Agus (Journal of Teaching and Education, 2022)
This Classroom Action Research (CAR) was designed to examine the application of the "Problem Based Learning" model in improving the ability to understand the concept of human rights in Civics subjects for seventh grade students of SMP Neg. 29 Rumbia Bombana Regency. Human rights material taught in Civics is intended as an effort to increase students' knowledge and awareness of human rights. The aim is to prevent students from taking actions that are contrary to human rights and not discriminatory behavior based on differences so that human rights violations occur. With the problem based learning model, the teacher only directs effective and efficient strategies, namely learning how to learn (learning how to learn) but students can actively discuss solving problems presented by the teacher. As well as the teacher as a guide (provider of directions / instructions) to help students if they find difficulties in learning and solving problems. Based on the results of the study, it can be concluded that the Problem Based Learning model can improve students' ability to understand the concept of Human Rights in Citizenship Education lessons in class VII students in the even semester of the 2021/2022 academic year at SMP Neg. 29 Rumbia.